Blue Ear Cyst: A Rare Eccrine Hidrocystoma of the Ear Canal and Successful Endoscopic Excision - Taha A. Mur; Ronald Miick; Natasha Pollak (Case Reports in Otolaryngology)
Aims. Hidrocystomas are benign cystic growths of the apocrine and eccrine sweat glands. These cystic lesions have been well documented on the face, head, and neck, but rarely in the external auditory canal. Presentation of Case. A 67-year-old woman presented with a bluish cystic mass partially occluding the external auditory canal and interfering with hearing aid use. Lesion was excised completely via a transcanal endoscopic approach with excellent cosmetic results, no canal stenosis, and no recurrence at 1-year follow-up. Discussion. We present a rare eccrine hidrocystoma of the external auditory canal and successful excision of this benign lesion. We describe the surgical management using a transcanal endoscopic approach and follow-up results. An eccrine gland cyst that presents as a mass occluding the external auditory canal is quite rare. There are only a few such cases reported in the literature. These masses can be mistaken for basal cell carcinomas or cholesterol granulomas but can be easily differentiated using histopathology. Conclusion. Eccrine hidrocystoma is a cystic lesion of sweat glands, rarely found in the external auditory canal. A characteristic bluish hue aids in diagnosis and surgical excision using ear endoscopy provides excellent control.